Analisis Yuridis Putusan Pengadilan Negeri Sidoarjo Nomor 13/Pid.Sus-Anak/2019/Pn.Sda tentang Perlindungan Anak sebagai Kurir Narkoba - Maharani, Yuniar Carmelia; Rosnawati, Emy (Indonesian Journal Publisher, 2023)
Drug trafficking is increasing in Indonesia even to an alarming level, causing increasingly complex problems. Illegal drug trafficking is an activity or series of activities carried out against the law or without the rights stipulated as a criminal act. This study aims to determine whether the judge's decision Number 13/Pid.Sus-Anak/2019/PN.Sda is in accordance with the Law or not. Number 35 of 2014 concerning Child Protection and Law no. 11 of 2012 concerning the Juvenile Justice System in terms of fulfilling children's rights in the judicial process. The research method that the author uses is a normative juridical approach using a case approach or commonly known as a case approach. The results of this study explain that the judge's consideration of the actions of child perpetrators is regulated and is subject to criminal sanctions in Article 114 paragraph (1) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics. However, there is a discrepancy with Law No. 35 of 2014 and Law no. 11 of 2012. The analysis of legal materials used is deductive reasoning analysis, namely the preparation using hypotheses or temporary answers. This study applies a pattern in the form of a general phenomenon drawn to a specific conclusion.